Analysis Of Service Quality In Early Child Care Services Businesses Using Servqual And Quality Function Deployment - Pratama, Muhammad Rengga Arya; Hidayat, Hidayat; Negoro, Yanuar Pandu (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to analyse the quality of childcare services by considering local wisdom and traditional games and conducting a case study at OMAH BOCAH. The SERVQUAL method measures parents' perceptions of the quality of services provided. In contrast, the QFD method is used to design childcare programs that align with parents' needs and expectations, taking into account local wisdom and environmental values. Uniqueness of traditional games. This research uses a qualitative approach with data collection techniques through observation, interview, and documentation studies. The collected data was then analysed using qualitative analysis methods to identify key factors of service quality implemented at OMAH BOCAH. Furthermore, the QFD method designs a higher quality and sustainable childcare program by integrating local wisdom and traditional games. The results of this research will provide a deeper understanding of how local wisdom and traditional games can improve the quality of childcare services. Thus, this research can provide useful recommendations for other childcare service providers to integrate aspects of local wisdom and the uniqueness of traditional games to improve the quality of their services. Keywords: local wisdom, traditional games, Servqual method, QFD